People's Advocate or Parliament's Advocate? Some considerations concerning the effects of the Constitutional Court of Romania's Ruling no.455/2021 - Popa, Nicolae-Alexandru (Technium Social Sciences Journal, 2023)
The study gravitated around the institution of the Ombudsman or Avocatul Poporului – the name that the Romanian constituent opted. The constitutional regulation can be found in Chapter IV of Title II - "Fundamental rights, freedoms and duties", and not in Title III - "Public authorities". The constituent legislator regulated the People’s Advocate institution distinctly and beyond the three powers - legislative, executive and judicial, with the aim of supporting the achievement of balance of powers in the state, for the benefit of individuals and of their rights that People’s Advocate is required to defend. On June 16th, 2021, the Romanian Parliament, during the joint session of the Chamber of Deputies and the Senate, adopted Decision no. 36/16.06.2021 for the revocation of Mrs. Renate Weber from the position of People's Advocate. After the day on which the People's Advocate was revoked from her position, one of the parliamentary parties filed an unconstitutionality notification concerning Parliament Decision no. 36/2021, registered at the Constitutional Court of Romania under number 5118 of June 17th, 2021, thus constituting File no. 2097L/2/2021.